FPGA Implementation of ML, ZF and MMSE Equalizers for MIMO Systems - Trimeche, Abdessalem; Sakly, Anis; Mtibaa, Abdellatif (Procedia computer science, 2015)
This paper presents an FPGA implementation of Maximum likelihood (ML), zero forcing (ZF) and minimum mean squared error (MMSE) equalizers applied to wireless multi-input multi-output (MIMO) systems with no fewer receive than transmit antennas. In spite of much prior work on this subject, we reveal several new and surprising analytical results in terms of output signal-to-noise ratio (SNR), by comparing the Bit Error Rate (BER) and the average detection time consuming. Results based on the platform of Xilinx Virtex 6. We discuss the case where there a multiple transmit antennas and multiple receive antennas resulting in the formation of a Multiple Input Multiple Output (MIMO) channel with Zero Forcing equalizer, MIMO with MMSE equalizer, MIMO with ZF Successive Interference Cancellation equalizer, MIMO with ML equalization, MIMO with MMSE SIC and optimal ordering.